Salt tolerance classification of crops according to soil salinity and to water stress day index - Katerji N.; van Hoorn I.W.; Hamdy A.; Mastrorilli M. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
The observations of a long-term experiment on the use of saline water used to compare the crop tolerance to salinity. Salinity affected significantly yield, evapotranspiration, pre-dawn leaf water potential and stomatal conductance. The higher the salinity, the lower the yield, evapotranspiration, pre-dawn leaf water potential and stomatal resistance. The crop classification, based on soil salinity, corresponds with the classification of Maas and Hoffman: sugarbeet and durum wheat as salt tolerant, braoadbean, maize, potato, sunflower and tomato as moderately salt sensitive. The difference with respect to soybean, classified as moderately salt sensitive instead of moderately salt tolerant can be ascribed to difference in variety. Weather conditions affected strongly the salt tolerance of broadbean. The water stress day index was also used for salt tolerance classification. According to this method, maize, sunflower and potato were included in the same salt tolerant group as sugarbeet and durum wheat. The previous classification of maize and sunflower as moderately sensitive is caused by the fact that these crops are grown during a period of higher evaporative demand than when sugarbeet and durum wheat are grown. The change of potato from moderately sensitive to salt tolerant may be ascribed to its shallow root system.